The identification of two M20B family peptidases required for full virulence in Staphylococcus aureus - Torres, Nathanial J.; Rizzo, Devon N.; Reinberg, Maria A.; Jobson, Mary-Elizabeth; Totzke, Brendan C.; Jackson, Jessica K.; Yu, Wenqi; Shaw, Lindsey N. (Frontiers in Cellular and Infection Microbiology, 2023)
We have previously demonstrated that deletion of an intracellular leucine aminopeptidase results in attenuated virulence of S. aureus. Herein we explore the role of 10 other aminopeptidases in S. aureus pathogenesis. Using a human blood survival assay we identified mutations in two enzymes from the M20B family (PepT1 and PepT2) as having markedly decreased survival compared to the parent. We further reveal that pepT1, pepT2 and pepT1/2 mutant strains are impaired in their ability to resist phagocytosis by, and engender survival within, human macrophages. Using a co-infection model of murine sepsis, we demonstrate impairment of dissemination and survival for both single mutants that is even more pronounced in the double mutant. We show that these enzymes are localized to the cytosol and membrane but are not necessary for peptide-based nutrition, a hallmark of cell-associated aminopeptidases. Furthermore, none of the survival defects appear to be the result of altered virulence factor production. An exploration of their regulation reveals that both are controlled by known regulators of the S. aureus virulence process, including Agr, Rot and/or SarA, and that this cascade may be mediated by FarR. Structural modeling of PepT1 reveals it bears all the hallmarks of a tripeptidase, whilst PepT2 differs significantly in its catalytic pocket, suggesting a broader substrate preference. In sum, we have identified two M20B aminopeptidases that are integral to S. aureus pathogenesis. The future identification of protein and/or peptide targets for these proteases will be critical to understanding their important virulence impacting functions.